Navigating Challenges: The Adaptation Process of Elementary School Teachers in Implementing Inclusive Education - Didi Pramono; Fulia Aji Gustaman; Anindhyta Putri Pradipta; Ismuwati (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2026)
Universitas Negeri Semarang, as a Teacher Education Institution, has developed an Elementary School Labschool to support its vision of educational excellence. However, challenges remain in implementing inclusive education at the school. This study aims to analyze (1) the process of teacher adaptation in implementing inclusive education, (2) teachers’ strategies for developing inclusive education competencies, and (3) supporting and inhibiting factors affecting implementation. Data were collected through interviews, focus group discussions, observations, and documentation, and were analyzed qualitatively using source triangulation to ensure validity. The findings show that teachers adapt through appraisal and employ coping strategies, including problem-focused coping—such as participating in training programs and developing Individualized Education Programs (IEPs)—and emotion-focused coping through emotional regulation, positive affirmation, and collaboration with support teachers. Teacher competency development strategies include formal training, in-house training, independent learning via digital platforms, and the enhancement of social-emotional skills. Supporting factors include government policies, institutional facilities, and professional development programs, while inhibiting factors involve limited disability-friendly infrastructure, administrative workload, unsustainable training, and constraints in initial student assessment. The study concludes that the successful implementation of inclusive education depends on the synergy among teacher readiness, policy support, and adequate facilities.